The Effect of Desmopressin on Reducing Blood Loss in Cardiac Surgery – A Meta-Analysis of Double-Blind, Placebo-Controlled Trials - Cattaneo, Marco; Harris, Alan S; Strömberg, Ulf; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1995)
The effect of desmopressin (DDAVP) on reducing postoperative blood loss after cardiac surgery has been studied in several randomized clinical trials, with conflicting outcomes. Since most trials had insufficient statistical power to detect true differences in blood loss, we performed a meta-analysis of data from relevant studies. Seventeen randomized, double-blind, placebo-controlled trials were analyzed, which included 1171 patients undergoing cardiac surgery for various indications; 579 of them were treated with desmopressin and 592 with placebo. Efficacy parameters were blood loss volumes and transfusion requirements. Desmopressin significantly reduced postoperative blood loss by 9%, but had no statistically significant effect on transfusion requirements. A subanalysis revealed that desmopressin had no protective effects in trials in which the mean blood loss in placebo-treated patients fell in the lower and middle thirds of distribution of blood losses (687-1108 ml/24 h). In contrast, in trials in which the mean blood loss in placebo-treated patients fell in the upper third of distribution (>1109 ml/24 h), desmopressin significantly decreased postoperative blood loss by 34%. Insufficient data were available to perform a sub-analysis on transfusion requirements. Therefore, desmopressin significantly reduces blood loss only in cardiac operations which induce excessive blood loss. Further studies are called to validate the results of this meta-analysis and to identify predictors of excessive blood loss after cardiac surgery.